Knowledge of Inhaler Therapy among Undergraduates and Resident Doctors in Tertiary Care Hospital, Nepal - Dev Shrestha, Bhakta; Dhungana, Ashesh; Shrestha, Prajwol; Raj Thapa, Kamal; Sahani, Bikash; Dhodary, Shyam (Nepalese Respiratory Journal, 2022)
Introduction: Inhalation therapy is the administration of the aerosolized medication directly into the lungs and it is the most effective form of management of the obstructive airway disease including chronic obstructive airway disease, asthma and overlap syndrome. There is less data on the knowledge of inhaler therapy among the junior doctors who are managing obstructive airway disease at the first contact point. This study was done to assess the knowledge of undergraduate doctors and resident doctors who are treating the patients before the consultation with senior consultants working in one of the tertiary care hospital . The findings of the study will help find the strategies of filling the gaps of the knowledge of inhalation therapy among junior doctors while managing obstructive airway disease Objective: The primary objective of the study was to find the Knowledge of Inhaler Therapy among Undergraduates and Resident doctors in Bir Hospital. Methods: The study was a cross sectional questionnaire based descriptive study conducted in Bir Hospital, National Academy of medical Sciences. The study included purposeful sampling of the medical officers and residents working in medical ward and emergency. Results: Out of 70 respondents, 79% and 82% percent responded the correct method of the administration of the DPIs and MDIs respectively. Forty percent of the respondents had heard of the breath actuated devices and 88% of the respondents had heard of the spacer device. Forty one percent of the respondents said they teach the patients about the method of inhalation technique while prescribing the inhalation therapy. Seventy three percent of the respondents thought inhaler therapy as the first line therapy for managing COPD and Asthma. Conclusion: Prescription of inhalers, knowledge among junior MBBS undergraduate doctors regarding inhalation therapy, and correct use of inhalers varied, and was generally inadequate. More effort, academic training and exposure is needed to change the attitude of medical officers and residents regarding the concept of inhalation therapy.